2019
DOI: 10.3390/medicines6020050
|View full text |Cite
|
Sign up to set email alerts
|

Increased Functional Foods’ Consumption and Mediterranean Diet Adherence May Have a Protective Effect in the Appearance of Gastrointestinal Diseases: A Case–Control Study

Abstract: Background: Epidemiological studies have suggested a possible correlation between nutritional factors and gastrointestinal diseases. Methods: A case–control study was designed in order to investigate if functional foods consumption and Mediterranean diet adherence have a positive effect in ulcerative colitis, Crohn’s disease, irritable bowel syndrome, and gastroesophageal reflux disease. In total, 142 patients (cases) and 147 gender-matched healthy people (controls) participated in the study. Functional food c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 37 publications
0
38
0
2
Order By: Relevance
“…Regarding the potential association of MD adherence with FGIDs, data in adults support a beneficial effect of the MD on the onset of gastrointestinal (GI) symptoms in patients with GI disease, both organic (inflammatory bowel disease) and functional (IBS, functional dyspepsia, gastroesophageal reflux) [35]. A case-control study in adult patients with ulcerative colitis, Crohn’s disease, IBS, or gastroesophageal reflux, showed that consumption of functional foods, including probiotics, prebiotics, antioxidants, fiber, vitamins, minerals, etc., and adherence to the MD was lower in patients than in controls [36]. A study from Southern Italy by Zito et al [37] investigated the association between adherence to the MD and onset of symptoms in adults with functional dyspepsia or IBS.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the potential association of MD adherence with FGIDs, data in adults support a beneficial effect of the MD on the onset of gastrointestinal (GI) symptoms in patients with GI disease, both organic (inflammatory bowel disease) and functional (IBS, functional dyspepsia, gastroesophageal reflux) [35]. A case-control study in adult patients with ulcerative colitis, Crohn’s disease, IBS, or gastroesophageal reflux, showed that consumption of functional foods, including probiotics, prebiotics, antioxidants, fiber, vitamins, minerals, etc., and adherence to the MD was lower in patients than in controls [36]. A study from Southern Italy by Zito et al [37] investigated the association between adherence to the MD and onset of symptoms in adults with functional dyspepsia or IBS.…”
Section: Discussionmentioning
confidence: 99%
“…However, nutritional and health claims about the possible effect of functional foods on disease prevention has been established only in specific situations, when sufficient scientific data ensure their properties. Furthermore, the scientific research concludes that functional foods may have beneficial effects in human health only if they are part of a balanced diet, such as the Mediterranean diet [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The Mediterranean diet has also been recognized as a possible protective factor in the prevention of CAD. This diet is characterized by high consumption of vegetables, fruits, olive oil, cereals, fishes and low consumption of meat and saturated fats [ 17 , 18 , 19 ]. Several studies have concluded that specific functional foods of the Mediterranean diet may have a protective effect against atherosclerotic process and thus CAD development.…”
Section: Introductionmentioning
confidence: 99%